IMPLEMENTATION OF CHARACTER EDUCATION THROUGH CHILD- FRIENDLY SCHOOL PROGRAMS - Vika Ardian, Vika Ardian; Khoirunnisa, Khoirunnisa; Muhammad Abel Ramadhan, Muhammad Abel Ramadhan; Ida Afi Ratna Sari, Ida Afi Ratna Sari; Riska Ardi Widyanti, Riska Ardi Widyanti; Atmojo, Setyo Eko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Peradaban, 2026)
This study aims to analyze character education practices in schools with child-friendly policies. The method used was descriptive qualitative with a short sentence. The results of interviews and observations yielded phenomenological results. Data collection techniques were conducted through interviews, observations, and documentation using source triangulation involving the principal, teachers, and students. The research results show that the implementation of Child-Friendly School-based character education has been carried out through various programs such as fostering discipline, religous activities, strengthening social values, and creating a safe and comfrotable learning environment for students. Furthermore, the active participation of all school members significantly supports the program`s success. However, several obstacles remain, sucg as limited supporting facilities and a lack of consistency in policy implementation. Therefore, it can be concluded that the practice of character education through the Child-Friendly School policy has a positive impact on the formation of student attitudes and behavior.